2020
DOI: 10.3390/diagnostics10090673
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery in COVID-19 Era—Safety and Ethical Issues

Abstract: (1) Background:The paper aims to review the available evidence regarding the health risk of the aerosolization induced by laparoscopy induced and impact of the COVID-19 pandemic upon minimally invasive surgery.(2) Materials and methods: A systematic review of the literature was performed on PubMed, Medline and Scopus until July 10th. (3) Results: Chemicals, carcinogens and biologically active materials, such as bacteria and viruses, have been isolated in surgical smoke. However, the only evidence of viral tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Positive pressure in the operating room is off. The operation is performed by open surgical approach, avoiding laparoscopy in patients who could not be delayed until obtaining the RT-PCR result, according to initial ARCE recommendations, to avoid possible aerosolization of viral particles, in the absence of a pneumoperitoneum filtration system (8)(9)(10)(11)(12)(16)(17)(18). This has led to a significant decreased use of laparoscopy in emergency during the COVID-19 pandemic (P=0.0234).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive pressure in the operating room is off. The operation is performed by open surgical approach, avoiding laparoscopy in patients who could not be delayed until obtaining the RT-PCR result, according to initial ARCE recommendations, to avoid possible aerosolization of viral particles, in the absence of a pneumoperitoneum filtration system (8)(9)(10)(11)(12)(16)(17)(18). This has led to a significant decreased use of laparoscopy in emergency during the COVID-19 pandemic (P=0.0234).…”
Section: Resultsmentioning
confidence: 99%
“…Infection modalities confirmed by clinical trials are through droplets, aerosols, direct and indirect contact (6,7). To prevent in-hospital contamination of medical personnel, the new protocol guidelines recommend avoiding all medical-surgical procedures with the potential to generate aerosols in suspected infected individuals or whose COVID-19 status has not yet been evaluated, including endoscopy and laparoscopy, and performing them with appropriate protective equipment, only when the benefit to the patient outweighs the risk (8)(9)(10)(11)(12)(13)(14)(15)(16). This has a significant impact on the management of acute abdomen, a clinical entity of special severity, whose Acute surgical abdomen during the COVID-19 pandemic: Clinical and therapeutic challenges investigation and surgical approach does not allow a time delay until obtaining the result of RT-PCR testing for SARS-Cov-2.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 pandemic has a deep impact on the social and economic life worldwide and is considered the most severe sanitary crisis since the Spanish flu, a hundred years ago (22). In the present case, diabetes, the delayed dental treatment due to the fear of getting infected with COVID-19, as well as the relative delays in getting appointments to specialized outpatient clinics, in the presence of insufficient and incomplete antibiotic self-medication caused the development of a torpid infectious process (23).…”
Section: Discussionmentioning
confidence: 99%
“…He reported that laparoscopic surgery can be safely performed. 35,36 Similarly Galvez A did laparoscopic surgery for perforated peptic ulcer in a patient having COVID -19 pneumonia with use of PPE and HEPA filter. Operation theater staff did not contract COVID -19 infection.…”
Section: Discussionmentioning
confidence: 99%